2014
DOI: 10.1021/jm500457x
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationships of Privileged Structures Lead to the Discovery of Novel Biased Ligands at the Dopamine D2 Receptor

Abstract: Biased agonism at GPCRs highlights the potential for the discovery and design of pathway-selective ligands and may confer therapeutic advantages to ligands targeting the dopamine D2 receptor (D2R). We investigated the determinants of efficacy, affinity, and bias for three privileged structures for the D2R, exploring changes to linker length and incorporation of a heterocyclic unit. Profiling the compounds in two signaling assays (cAMP and pERK1/2) allowed us to identify and quantify determinants of biased agon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 32 publications
0
78
1
Order By: Relevance
“…An advantage of the operational model as applied to SAR is that it can almost always be fitted to experimentally derived data to provide estimates of some, or all, of its parameters with regards both to allosteric modulators (Aurelio et al, 2009;Gregory et al, 2012;Valant et al, 2012a;Huynh et al, 2013;Mistry et al, 2013) and biased agonists (Tschammer et al, 2011b;Shonberg et al, 2013;Szabo et al, 2014). Table 1 illustrates an example of allosteric modulator SAR determined through analysis of the effects of various thienopyridine modulators on acetylcholine-mediated ERK1/2 phosphorylation at the M 4 mAChR.…”
Section: Advances In Gpcr Allosterymentioning
confidence: 99%
“…An advantage of the operational model as applied to SAR is that it can almost always be fitted to experimentally derived data to provide estimates of some, or all, of its parameters with regards both to allosteric modulators (Aurelio et al, 2009;Gregory et al, 2012;Valant et al, 2012a;Huynh et al, 2013;Mistry et al, 2013) and biased agonists (Tschammer et al, 2011b;Shonberg et al, 2013;Szabo et al, 2014). Table 1 illustrates an example of allosteric modulator SAR determined through analysis of the effects of various thienopyridine modulators on acetylcholine-mediated ERK1/2 phosphorylation at the M 4 mAChR.…”
Section: Advances In Gpcr Allosterymentioning
confidence: 99%
“…For D 1 receptor several studies were performed describing the effects of structural dissimilar D 1 receptor agonists on homologous desensitization induced by a cAMPindependent pathway (Lewis et al, 1998;Ryman-Rasmussen et al, 2005), e.g., apomorphine showed a D 1 receptor biased ligand behavior on selective stimulation of Gprotein controlled pathway (cAMP accumulation by adenylyl cyclase activity) (Ryman-Rasmussen et al, 2005). Biased signaling for the D 2 receptor is mainly studied on antipsychotic drugs for the treatment for schizophrenia (Beaulieu et al, 2009;Clarke et al, 2013;Klewe et al, 2008;Masri et al, 2008;Shonberg and Lopez, 2014;Szabo et al, 2014). Interestingly, many of these ligands are partial receptor agonists on the D 2 receptor and have structural similarities to aripiprazole.…”
Section: Dopamine D 3 Receptor Agonist Signalingmentioning
confidence: 99%
“…Hence, it is most likely that (R,R')-4 0 -aminofenoterol adopts a dualsteric binding topography as well, which might be responsible for its G s bias. Moreover, three recent studies at the dopamine D 2 receptor present a set of biased ligands and suggest that the ligand bias might result from a dualsteric binding mode [65][66][67]. In addition, a recent crystal structure from another aminergic receptor family member, the serotonin 5-HT 2B receptor in complex with the b-arrestin biased ligand ergotamine, showed that ergotamine engages epitopes from extracellular parts of the receptor, a topography which the authors term an 'extended binding mode' [57,68].…”
Section: Fine-tuning Gpcr Signalingmentioning
confidence: 99%